TEST AND APPLICATION OF THE TIME- AND MAGNITUDE PREDICTABLE-MODEL TO THE INTERMEDIATE AND DEEP FOCUS EARTHQUAKES IN THE SUBDUCTION ZONES OF THE CIRCUM-PACIFIC BELT - Papadimitriou E.E.; Papazachos C.B.; Tsapanos T.M. (My University, 2001)
The test and application of the time and magnitude predictable model in the subduction zones around the circum-Pacific belt is performed. Each subduction zone was separated in several seismogenic regions on the basis of tectonic and geometrical features of the subducting lithosphere and for three different depth ranges. The data derived from these seismogenic regions were used in order to check the suitability of the regional time and magnitude predictable model, as this model was defined for shallow events. The results obtained in the present study confirm that this model appropriately describes the behavior of deep seismicity in these regions, since a positive (c=0.31+/-0.003) and a negative (C=-0.13+/-0.047) dependence were found for the logarithm of the interevent times and the magnitude of following mainshock, respectively, on the magnitude of the preceding mainshock. Moreover, the slip-predictable model was rejected, since a negative dependence was found (E=-0.19) between the interevent times and the magnitudes of the following mainshock. Probabilities of occurrence of the future strong (M=<7.0) events in each seismogenic region have been determined for the next decade conditioned on the previous occurrence of such events. The magnitudes of the expected events have also been estimated. Statistical tests for the estimated probabilities exhibit a good correlation with the occurrence rate of such events. Furthermore, the statistical significance of the model has been studied through additional tests. The results of this study demonstrate the validity of the regional time and magnitude predictable model in the areas examined.
Keywords: TIME- AND MAGNITUDE-PREDICTABLE MODEL; SUBDUCTION ZONES; CIRCUM-PACIFIC BELT; CONDITIONAL PROBABILITIES; STATISTICAL SIGNIFICANCE